PENGARUH PROMOSI, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA MIE NYINYIR NGANJUK - Atmaja, Via Amalia Wira (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to determine: 1) The effect of partial promotion on the decision of Mie Nyinyir Nganjuk. 2) The partial effect of brand image on purchasing decisions of Nyinyir Nganjuk Noodles. 3) The effect of service quality partially on purchasing decisions of Nyinyir Nganjuk Noodles. 4) Identify and analyze the simultaneous influence of promotion, brand image and service quality on purchasing decisions of Mie Nyinyir Nganjuk. The type of research used in this research is quantitative with causal research techniques. The population is all consumers who have consumed Nyinyir noodle products, the number of population members is generally unknown. The sample of this research is 60 respondents with Rescoe technique. The type of instrument used in this study is a questionnaire. The data analysis technique used multiple linear regression t-test and F-test. The results showed that: 1) There was no partial effect of promotion on purchasing decisions of Nyinyir Nganjuk Noodles. 2) There is no partial effect of brand image on purchasing decisions of Nyinyir Nganjuk Noodles. 3) There is a partial influence of service quality on purchasing decisions of Nyinyir Nganjuk Noodles. 4) There is a simultaneous influence of promotion, brand image and service quality on the purchasing decision of Mie Nyinyir Nganjuk. It was concluded that: the most influential variable of promotion, brand image and service quality is service quality on purchasing decisions.